Corded and hyalinized endometrioid carcinoma: a case report and literature review - Liu, Rong; Wang, Yani; Shi, Weichen; Wang, Yanan; Hu, Jiangong (Frontiers in Oncology, 2026)
Corded and hyalinized endometrioid carcinoma (CHEC) is a rare morphological subtype of endometrioid carcinoma (EC), characterized by a biphasic pattern consisting of epithelial or spindled tumor cells embedded within hyalinized stroma, merging with conventional low-grade EC. We present a case of CHEC in a 24-year-old woman who presented with irregular vaginal bleeding. Imaging showed a mass protruding toward the cervix, and subsequent tumor resection confirmed the diagnosis of CHEC. Immunohistochemical staining for β-catenin and CTNNB1 gene mutation analysis were helpful in the diagnosis of CHEC, and molecular subtyping provided valuable prognostic information to a certain extent. Postoperatively, the patient received progestin therapy for 6 months and remained recurrence-free. Given the rarity of CHEC, distinguishing this disease from other biphasic uterine tumors is crucial. This report aims to enhance recognition of this rare entity, facilitating its accurate diagnosis and preventing inappropriate therapeutic interventions.